Karakteristik Fisikokimia dan Kapasitas Antioksidan Kopi Liberika dari Kabupaten Tanjung Jabung Barat, Jambi - Dirayati Hanifah; Dian Herawati; Nuri Andarwulan (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2022)
Liberica coffee is one of the coffee species in commercial trade in Indonesia. The coffee is produced in Tanjung Jabung Barat Regency, Jambi, Indonesia which distributed into 5 sub-districts (Betara, Bram Itam, Kuala Betara, Pengabuan, Senyerang). Information about liberica coffee from Jambi is still limited, thus more exploration is needed. The objectives of this study were to characterize the morphology of the leaf and fruit, the physicochemical characteristics which include the dimension (length, width, thickness), mass, bulk density, colour (L*, a*, b*), moisture contents, TSS (total soluble solids), pH, and antioxidant capacity (DPPH IC50, FRAP) of green and roasted (commercial level) liberica coffee from the above 5 sub-districts. The studies showed that liberica coffee from 5 sub-districts in Tanjung Jabung Barat Rgency, Jambi had various leaf and fruit appearances which were characterized by various size and colour of coffee cherries. Green coffee from different sub-districts owned various physicochemical (width, volume, mass, bulk density, moisture content, TSS) and antioxidant capacity of green coffee. Green coffee from Betara and Pengabuan were associated with high TSS, L* and b* value, while green coffee from Bram Itam and Senyerang were associated with high mass, moisture content and a* value. The highest anti-oxidant capacity was produced by green coffee from Betara and Kuala Betara (DPPH IC50). Meanwhile, roasted coffee produced from green coffee from the 5 sub-districts with similar roasting level (similar L*) produced similar a*, b* value, mass and TSS. However, physicochemical characteristics (length, width, volume, bulk density, moisture content) and antioxidant capacity of these roasted beans varied.